Hubungan Status Gizi dengan Perkembangan Motorik Halus Pada Anak Usia Pra Sekolah - Yulia Wulandari; Iis Aisyah; Amanda Puspanditaning (Jurnal Keperawatan Florence Nightingale, 2024)
One of the things that influences how well children develop their fine motor skills is their nutritional condition. Children who are malnourished can have impaired fine motor skills that are inappropriate for their age. The aim of this research is to find out the relationship between the fine motor development of preschool children in Margamukti Village and their nutritional status. This research method used a cross-sectional quantitative research design and a total sample technique was used in this research with a total of 48 respondents; The population was children attending Kenanga Kindergarten, Margamukti Village, aged between 36 and 72 months. The SDIDTK questionnaire sheet was used to measure fine motor development, while anthropometric measurements of body weight based on age were used to determine nutritional status. The research results showed that there was no relationship between the fine motor development of preschool children in Margamukti Village and their nutritional status. A p value of 0.532 > (0.05) was found in the Spearman Rank test. The research results show that there is no relationship between the fine motor development of preschool children in Margamukti Village and their nutritional status. A p value of 0.532 > (0.05) was found in the Spearman Rank test. These results indicate that nutritional status does not have a significant influence on fine motor development in pre-school children in Margamukti Village.